Intraluminal Meckel's Duplication Cyst Causing Bowel Obstruction in an Infant: A Role for Laparotomy - Mitchell R. Ladd; Alejandro V. Garcia; Derek B. Allison; Jeffrey R. Lukish (Hindawi Limited, 2016)
This report describes a two-month-old girl who presented with signs and symptoms of a distal small bowel obstruction. She underwent an abdominal ultrasound that revealed a right lower quadrant cystic mass. A Technetium-99 scan revealed increased activity in the right lower quadrant consistent with a Meckel's diverticulum. Following a nondiagnostic laparoscopic evaluation, a laparotomy was performed to allow direct palpation of the small bowel and colon. Direct palpation of the ileum revealed a soft intraluminal mass at the ileocecal valve. The child underwent an ileocecectomy and anastomosis incorporating the intraluminal mass. Pathologic analysis revealed an intraluminal enteric duplication cyst containing ectopic gastric mucosa. This case represents the first report of such an entity in an infant. A discussion of the diagnostic and therapeutic aspects of the case and enteric duplication cysts is provided.